Deep learning for sex determination: Analyzing over 200,000 panoramic radiographs - Ciconelle, Ana Claudia Martins; da Silva, Renan Lucio Berbel; Kim, Jun Ho; Rocha, Bruno Aragão; dos Santos, Dênis Gonçalves; Vianna, Luis Gustavo Rocha; Gomes Ferreira, Luma Gallacio; Pereira dos Santos, Vinícius Henrique; Costa, Jeferson Orofino; Vicente, Renato (Journal of forensic sciences, 2023)
The objective of this study is to assess the performance of an innovative AI‐powered tool for sex determination using panoramic radiographs (PR) and to explore factors affecting the performance of the convolutional neural network (CNN). The study involved 207,946 panoramic dental X‐rays and their corresponding reports from 15 clinical centers in São Paulo, Brazil. The PRs were acquired with four different devices, and 58% of the patients were female. Data preprocessing included anonymizing the exams, extracting pertinent information from the reports, such as sex, age, type of dentition, and number of missing teeth, and organizing the data into a PostgreSQL database. Two neural network architectures, a standard CNN and a ResNet, were utilized for sex classification, with both undergoing hyperparameter tuning and cross‐validation to ensure optimal performance. The CNN model achieved 95.02% accuracy in sex estimation, with image resolution being a significant influencing factor. The ResNet model attained over 86% accuracy in subjects older than 6 years and over 96% in those over 16 years. The algorithm performed better on female images, and the area under the curve (AUC) exceeded 96% for most age groups, except the youngest. Accuracy values were also assessed for different dentition types (deciduous, mixed, and permanent) and missing teeth. This study demonstrates the effectiveness of an AI‐driven tool for sex determination using PR and emphasizes the role of image resolution, age, and sex in determining the algorithm's performance.